Genocide and ecocide in four Colombian Indigenous Communities: the Erosion of a way of life and memory - Rodríguez Goyes, David (The British journal of criminology, 2021)
Generally, the traditional Indigenous ways of ‘knowing and seeing’ the natural world lead to more protective behaviours than the dominating economic approach that represents the interests of the global North. Indigenous ways of living and remembering are however, currently threatened with erosion by several global dynamics. While many of the most powerful forces involved in the extinguishment of Indigenous peoples and their cultures are visible and direct forms of violence, there are also structural, systemic and invisible factors at play. In this article, based on original primary data collected within communities of four Colombian Indigenous peoples, we identify the four main silent dynamics producing the extinction of Indigenous cultures in Colombia. We refer to the operation of these forces as a form of genocide and connect them to the simultaneous occurrence of an ecocide.